2021
DOI: 10.1097/inf.0000000000003372
|View full text |Cite
|
Sign up to set email alerts
|

Oral Azithromycin Versus Doxycycline in the Treatment of Children With Uncomplicated Scrub Typhus

Abstract: Objectives: To compare the efficacy of azithromycin versus doxycycline in treatment of children with uncomplicated scrub typhus in terms of percentage of children who attained remission of fever after 72 hours of administration of first dose of the study drug, mean time taken to attain fever defervescence, normalization of laboratory parameters, resolution of hepatosplenomegaly and lymphadenopathy. Design: Interventional, open-labeled randomized controlled trial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…Most studies were reported from India ( n =5, 50%). There were five RCTs [ 18 , 21 , 25 – 27 ]. Four studies included only paediatric patients (less than 14-18 years) [ 21 , 22 , 24 , 25 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most studies were reported from India ( n =5, 50%). There were five RCTs [ 18 , 21 , 25 – 27 ]. Four studies included only paediatric patients (less than 14-18 years) [ 21 , 22 , 24 , 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…There were five RCTs [ 18 , 21 , 25 – 27 ]. Four studies included only paediatric patients (less than 14-18 years) [ 21 , 22 , 24 , 25 ]. The remaining six incorporated either adults or individuals of any age.…”
Section: Resultsmentioning
confidence: 99%
“…Our study results are in sync with the published literature. [11][12][13] In a recent open-label RCT conducted on uncomplicated scrub typhus, 13 no significant difference was observed between children who achieved fever remission after receiving AZ compared with those treated with DX. Patients who did not achieve defervescence after 72 hours of the interventional drug were labeled as treatment failure cases and were switched over to the alternate drug, but the outcome of these cases was not mentioned.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study in children with uncomplicated scrub typhus showed equal efficacy of DX and AZ. 13 Thus, there was limited but promising data regarding the efficacy of AZ for the treatment of pediatric scrub typhus. We hypothesized that AZ (10 mg/kg/day for 5 days) was noninferior to DX (2.2 mg/kg/dose BD for weight <40 kg and 100 mg BD for weight >40 kg for 7 days) for achieving defervescence in hospitalized children 1–14 years old suffering from scrub typhus.…”
mentioning
confidence: 99%
“…This is consistent with the adverse reaction rate (8.6%) described in a recent trial of doxycycline for the treatment of scrub typhus in children less than 13 years old, largely due to gastrointestinal symptoms. 7 Administering oral doxycycline with food may prevent these symptoms.…”
Section: Discussionmentioning
confidence: 99%